Saccharomycotina yeasts in humans, animals and the environment: A call for integrated one health action - Wing Yan Jacqueline Tam; Clement K.M. Tsui; Justin Beardsley; Vanessa R. Barrs (Fungal Biology Reviews, 2026)

Poultry by-product meal as a fishmeal replacement in finfish aquaculture: A scoping review - ShaSha Liu; Zongsheng Qiu; Fernando Y. Yamamoto; Peng Li; Delbert M. Gatlin III; Qiyou Xu; Clement R. de Cruz (Animal Feed Science and Technology, 2026)

Monitoring of Colorectal Cancer Screening Adherence Among African American Patients of North Florida Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Askal A. Ali; Sabrina L. Dickey; Matthew Vargas; Deloria R. Jackson; Ryan Mohorne; Tanvee Doddi; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2026)
In the United States, colorectal cancer (CRC) mortality rates are higher in African Americans compared to non-Hispanic whites, partly due to advanced stage cancer diagnosis. Timely CRC screening helps to increase CRC early detection and survival in this population. The objective of this monitoring study was to survey African American patients of Community Health Centers (CHC) in north Florida and to monitor CRC screening adherence (either stool-based or colonoscopy) after they had completed a clinical trial testing a screening education intervention. Seventy-nine African American patients who were between the ages of 45 and 64 years old at the time of initial trial recruitment completed a 24-month follow-up survey, and 44% reported stool-based CRC screening in the last year. Results from the general estimating equations (GEE) model found there was a statistically significant difference in CRC screening adherence by study arm at 24 months where the intervention group was less likely to be up to date than the usual care control (OR = 0.60, 95% CI 0.43–0.83). Married or partnered participants (OR = 1.52, 95% CI 1.31–1.77) and employed participants (OR = 1.34, 95% CI 1.17–1.53) were more likely to be adherent to screening, but female participants were less likely to be adherent (OR = 0.76, 95% CI 0.70–0.82). Participants with higher mistrust in doctors were less likely to have completed screening (OR = 0.93, 95% CI 0.88–0.99). The findings suggest the importance of screening outreach to unmarried, unemployed, female African Americans. The results of this monitoring study indicate one-on-one cancer education with a community health advisor and education on the availability and functionality of electronic patient portals have potential for increasing adherence to recommended CRC screening. The study has implications for measuring CRC screening adherence in community settings.

Modulatory effects of dietary soybean isoflavones on ovarian development and mitochondria function related indices in female Macrobrachium rosenbergii - Haoze Wang; Jianle Yang; Jiaqi Wang; Xiaorui Fan; Junyi Wang; Clement R. de Cruz; Houkuan Du; Jianhua Zhao; Qiyou Xu (Aquaculture International, 2026)

Metabolic and antioxidant responses to short-term lysophosphatidylcholine injection in Macrobrachium rosenbergii - Zongsheng Qiu; Jianle Yang; Xinyi Wei; Yuqiang Wei; Shasha Liu; Jianhua Zhao; Qiyou Xu; Clement R. de Cruz (Aquaculture International, 2026)

Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Evaluating poultry fat and crude palm oil blends on growth performance, fatty acid profile, lipid metabolism and antioxidant capacity in juvenile Asian seabass (Lates calcarifer) - Husna Shafin Izzah; Murni Karim; Annita Seok-Kian Yong; Jiun-Yan Loh; Yan Chen; Clement R. de Cruz (Animal Feed Science and Technology, 2026)

Developing a pedotransfer function for the prediction of nitrogen mineralization in the agricultural soils of Quebec - Chedzer-Clark Clement; R. Deragon; B. Heung; J. Dessureault-Rompré; M.O. Gasser; J.-B. Mathieu; D.L. Burton (Geoderma Regional, 2026)

Correction to: Thierry B.R. Chopin (1959–2024) – Innovator of Modern IMTA - S. M. C. Robinson; C. Yarish; A. Buschmann; J. Clements; B. A. Costa‑Pierce; A. Hamer; L. Hayashi; C. Hurd; A. Neori; S. Pang; C. Pearce; G. Reid; et al. (Journal of Applied Phycology, 2026)

Contribution of microcosm experiments to conservation science - Eleanor R. Stern; Peter A. Vesk; Chris C. Clements; Michael A. McCarthy (Conservation Biology, 2026)
Microcosms, or miniature experimental systems, have been used to develop models and theories in ecology. However, their contribution to conservation science is unclear. We explored the application, design, and impact of microcosms in conservation science from 469 systematically identified articles published from 1986 to 2023. We used generalized linear modeling to compare cumulative citations over time for each microcosm article with those of 71,738 nonmicrocosm articles in conservation science. We also surveyed the proportion of microcosm articles and nonmicrocosm articles focused on conservation science that were cited in policy documents. Two types of microcosms were used in conservation research: generalized microcosms (i.e., simplified analogies of systems used to test general theories and mathematical models) and specialized microcosms (i.e., recreations of specific ecosystems or species assemblages that test specific hypotheses). Microcosms were used to study biodiversity, invasive species, extinction, pollution, and climate change and were applied to a broad array of ecosystems and species. Microcosm experiments tended to be small (systems were liters in size or smaller) and conducted over short periods (weeks or months); could monitor study species for up to hundreds of generations; and had high sample replication. On average, microcosm studies were cited up to twice as often as nonmicrocosm studies 25 years after publication. Microcosm articles and nonmicrocosm articles focused on conservation science were cited in policy documents at similar rates to each other. We recommend that conservation science, which often focuses on urgent topics and rare or threatened ecosystems and species, may benefit from the manipulability and replicability that microcosms offer. Microcosm experiments may also be low risk for the study systems involved. Future uses of microcosms include providing experimental evidence and testing of conservation theories, models, and hypotheses.

Lecithin-enriched diet improves growth performance, lipid metabolism and disease resistance in giant river prawn (Macrobrachium rosenbergii) - Zongsheng Qiu; Qiyou Xu; Chou Min Chong; Clement R. de Cruz (Aquaculture, 2026)

Implications of extreme flooding events for dispersal of Reynoutria spp. (knotweeds) in the wake of climate change - Sarah Demian; Aidan Anderson; Jaylene Braithwaite; Lauren Mckenna; David R. Clements (Biological Invasions, 2026)

Assessment of fish protein hydrolysate as a substitute for fish meal in white shrimp diets: Impact on growth, immune response, and resistance against Vibrio parahaemolyticus infection - Hoang Trieu Quan Tran; Thi Hang Ho; Fan-Hua Nan; Chun-Hung Liu; Chou Min Chong; Clement R. de Cruz; Murni Karim; Ting-Jui Liu; I-Pei Kuo; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Land cover, drought, and dust emission in arid Succulent Karoo shrublands - Heleen C. Vos; Johanna R. von Holdt; Helga van der Merwe; Igshaan Samuels; Ute Schmiedel; Norbert Jürgens; Juliane Krenz; Mmoto L. Masubelele; Bavisha Koovarjee; Wolfgang Fister; Frank D. Eckardt; Clement Cupido; et al. (Aeolian Research, 2025)

Effect of Halamphora coffeaeformis supplementation in rice bran biofloc on the growth and survival of black tiger shrimp (Penaeus monodon) postlarvae - Mohd Ihsanuddin Ahmad; Muhammad Farhan Nazarudin; Hazwani Hanim Hasnan; Ninie Diana Baharuddin; Kamil Latif; Clement R. de Cruz; Murni Karim; Hui Teng Tan; Yam Sim Khaw; Jeffrey K. C. Lee; Ikhsan Natrah (Aquaculture International, 2025)

Thierry B.R. Chopin (1959–2024) – Innovator of Modern IMTA - S. M. C. Robinson; C. Yarish; A. Buschmann; J. Clements; B. A. Costa-Pierce; A. Hamer; L. Hayashi; C. Hurd; A. Neori; S. Pang; C. Pearce; G. Reid; et al. (Journal of Applied Phycology, 2025)

Co‐Extinctions and Co‐Compensatory Species Responses to Climate Change Moderate Ecosystem Futures - Thomas J. Williams; Clement R. Garcia; Jasmin A. Godbold; Philippe Archambault; Martin Solan (Global Change Biology, 2025)
Consensus has been reached that the sequential loss of biodiversity leads to a non‐linear and accelerating decline in ecosystem properties. The form of this relationship, however, is based on theory and empirically derived observations that do not include species co‐extinctions. Here, we use data from marine benthic invertebrate communities to parameterise trait‐based extinction models that adjust the probability of species extirpation and compensation by including the dependencies between different species across a gradient of climate‐driven environmental change. Our simulations reveal that the inclusion of static co‐extinctions leads to more pronounced declines in the trajectories of sediment bioturbation—a process of great importance to the functioning of marine ecosystems—than those observed with sequential losses of single species. Compensatory mechanisms and the allowance of the formation of new interactions derived from local and regional species pools moderate the compounding influence of co‐extinction but introduce additional variability in community response depending on the composition and functional role of incoming and outgoing species. Our observations emphasise the importance of accounting for local and regional community dynamics, especially in highly connected systems that are prone to extinction cascades when projecting the ecosystem consequences of altered biodiversity.

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Agronomic and environmental effects of forage-cutting schedule and nitrogen fertilization for bermudagrass (Cynodon dactylon, L.) - Clement D.D. Sohoulande; Liwang Ma; Zhiming Qi; Ariel Szogi; Kenneth Stone; Daren R. Harmel; Jerry H. Martin; Girma Birru; Matthew Sima (Agriculture, Ecosystems & Environment, 2025)

Leopards on the edge: Assessing population status, habitat use, and threats in Southeast Asia - S. Rostro-García; J.F. Kamler; R. Sollmann; G. Balme; R. Sukmasuang; A. Godfrey; S. Saosoong; K. Siripattaranukul; S. Suksavate; W. Thomas; R. Crouthers; V. In; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Industrial symbiosis and eco-industrial transformation opportunities for environmental protection in Nigeria - Abubakar M. Bilyaminu; Eldon R. Rene; Ashok Pandey; Sandhya Babel; Quinnetta Blessing Clement; Anina James; Hector Garcia Hernandez (Sustainable Production and Consumption, 2024)

Assessment of fish protein hydrolysate as a substitute for fish meal in white shrimp diets: Impact on growth, immune response, and resistance against Vibrio parahaemolyticus infection - Hoang Trieu Quan Tran; Thi Hang Ho; Fan-Hua Nan; Chun-Hung Liu; Yeh-Fang Hu; Chou Min Chong; Clement R. de Cruz; Murni Karim; Ting-Jui Liu; I-Pei Kuo; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

The impact of simulated total surface current velocity observations on operational ocean forecasting and requirements for future satellite missions - Jennifer Waters; Matthew J. Martin; Isabelle Mirouze; Elisabeth Rémy; Robert R. King; Lucile Gaultier; Clement Ubelmann; Craig Donlon; Simon Van Gennip (Frontiers in Marine Science, 2024)
Operational forecasts rely on accurate and timely observations and it is important that the ocean forecasting community demonstrates the impact of those observations to the observing community and its funders while providing feedback on requirements for the design of the ocean observing system. One way in which impact of new observations can be assessed is through Observing System Simulation Experiments (OSSEs). Various satellite missions are being proposed to measure Total Surface Current Velocities (TSCV). This study uses OSSEs to assess the potential impact of assimilating TSCV observations. OSSEs have been performed using two global ocean forecasting systems; the Met Office’s (MetO) Forecasting Ocean Assimilation Model and the Mercator Ocean International (MOI) system. Developments to the individual systems, the design of the experiments and results have been described in two companion papers. This paper provides an intercomparison of the OSSEs results from the two systems. We show that global near surface velocity analysis root-mean-squared-errors (RMSE) are reduced by 20-30% and 10-15% in the MetO and MOI systems respectively, we also demonstrate that the percentage of particles forecast to be within 50 km of the true particle locations after drifting for 6 days has increased by 9%/7%. Furthermore, we show that the global subsurface velocities are improved down to 1500m in the MetO system and down to 400m in the MOI system. There are some regions where TSCV assimilation degrades the results, notably the middle of the gyres in the MetO system and at depth in the MOI system. Further tuning of the background and observation error covariances are required to improve performance in these regions. We also provide some recommendations on TSCV observation requirements for future satellite missions. We recommend that at least 80% of the ocean surface is observed in less than 4 to 5 days with a horizontal resolution of 20 to 50 km. Observations should be provided within one day of measurement time to allow real time assimilation and should have an accuracy of 10 cm/s in the along and across track direction and uncertainty estimates should be provided with each measurement.

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Evaluation of diatom Halamphora sp. and harpacticoid copepod Amphiascoides neglectus as live food for black tiger shrimp Penaeus monodon postlarvae - Ninie Diana Baharuddin; Sarmila Muthukhrisnan; Clement R. de Cruz; Zaleha Kassim; Hazwani Hanim Hasnan; Mohd Ihsanudin Abdullah; Yam Sim Khaw; Hui Teng Tan; Muhammad Farhan Nazarudin; I. Natrah (Aquaculture, 2024)

Detecting climate‐related shifts in lakes: A review of the use of satellite Earth Observation - Elisa Calamita; J. Jelle Lever; Clement Albergel; R. Iestyn Woolway; Daniel Odermatt (Limnology and Oceanography, 2024)
Climate change exerts a profound impact on lakes, eliciting responses that range from gradual to abrupt transitions. When reaching critical tipping points, the established lake dynamics stand to undergo substantial modifications, setting off a chain reaction that reverberates through the entire ecosystem. This lake shift ripples into related ecosystem services and even influences the well‐being of human communities. Despite the importance of lake shifts, we lack a systematic overview of their occurrence, mainly due to the lack of systematic data at the global scale. We reviewed the literature focusing on climate‐related lake shifts and assessed how satellite Earth Observation (EO) has contributed to the research topic, and what we can unlock from this novel data. Our results show that EO data are used in only 9% of studies on lake shifts, although this fraction has increased since 2012. EO data is most commonly used to assess shifts in surface extent, ice coverage, or phytoplankton phenology. These variables are directly observable and the spatio‐temporal resolution of EO satellites is of great advantage. But lake shifts can also be identified indirectly from EO data, as in the example of the vertical mixing of lake water, which can be described on the basis of surface patterns. In all possible applications, we expect increasing use of EO satellites in the future, including the development of early warning systems that promise to provide timely alerts regarding impending lake shifts, thus serving as a vanguard against abrupt alterations that could ripple through interconnected ecosystem services.

Anti-inflammatory and antiproliferative activity of Helichrysum odoratissimum Sweet. against lung cancer - Tenille Esmear; Danielle Twilley; Velaphi Clement Thipe; Kattesh V. Katti; Vusani Mandiwana; Michel Lonji Kalombo; Suprakas Sinha Ray; Rirhandzu Rikhotso-Mbungela; Venugopal Reddy Bovilla; SubbaRao Madhunapantula; Lenka Langhanshova; Catarina Roma-Rodrigues; et al. (South African Journal of Botany, 2024)

Perceived constraints to participating in wildlife-related recreation - Nicholas W. Cole; Emily J. Wilkins; Kaylin R. Clements; Rudy M. Schuster; Ashley A. Dayer; H.W. Harshaw; David C. Fulton; Jennifer N. Duberstein; Andrew H. Raedeke (Journal of Outdoor Recreation and Tourism, 2024)

3D multi-cell-type liver organoids: A new model of non-alcoholic fatty liver disease for drug safety assessments - J. Bronsard; C. Savary; J. Massart; R. Viel; L. Moutaux; D. Catheline; V. Rioux; B. Clement; A. Corlu; B. Fromenty; P.J. Ferron (Toxicology in Vitro, 2024)

Inhibition of fatty acid binding protein-5 in the basolateral amygdala induces anxiolytic effects and accelerates fear memory extinction - Matthew J. Jones; Taygun C. Uzuneser; Timothy Clement; Hehe Wang; Iwao Ojima; Walter J. Rushlow; Steven R. Laviolette (Psychopharmacology, 2024)

Association of Preventive Care Attitudes and Beliefs with Colorectal Cancer Screening History among African American Patients of Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Matthew Vargas; Deloria R. Jackson; Olayemi O. Matthew; Tifini D. Austin; Rima Tawk; Askal A. Ali; Cynthia M. Harris; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2023)

Regional habitat suitability for aquatic and terrestrial invasive plant species may expand or contract with climate change - Emma Nikkel; David R. Clements; Delia Anderson; Jennifer L. Williams (Biological Invasions, 2023)
The threat of invasive species to biodiversity and ecosystem structure is exacerbated by the increasingly concerning outlook of predicted climate change and other human influences. Developing preventative management strategies for invasive plant species before they establish is crucial for effective management. To examine how climate change may impact habitat suitability, we modeled the current and future habitat suitability of two terrestrial species, Geranium lucidum and Pilosella officinarum , and two aquatic species, Butomus umbellatus and Pontederia crassipes , that are relatively new invasive plant species regionally, and are currently spreading in the Pacific Northwest (PNW, North America), an area of unique natural areas, vibrant economic activity, and increasing human population. Using North American presence records, downscaled climate variables, and human influence data, we developed an ensemble model of six algorithms to predict the potential habitat suitability under current conditions and projected climate scenarios RCP 4.5, 7.0, and 8.5 for 2050 and 2080. One terrestrial species ( P. officinarum ) showed declining habitat suitability in future climate scenarios (contracted distribution), while the other terrestrial species ( G. lucidum ) showed increased suitability over much of the region (expanded distribution overall). The two aquatic species were predicted to have only moderately increased suitability, suggesting aquatic plant species may be less impacted by climate change. Our research provides a template for regional-scale modelling of invasive species of concern, thus assisting local land managers and practitioners to inform current and future management strategies and to prioritize limited available resources for species with expanding ranges.

Hydrology drives export and composition of carbon in a pristine tropical river - Travis W. Drake; Matti Barthel; Christian Ekemba Mbongo; Davin Mata Mpambi; Simon Baumgartner; Clement Ikene Botefa; Marijn Bauters; Martin R. Kurek; Robert G. M. Spencer; Amy M. McKenna; Negar Haghipour; Godé Lompoko Ekamba; et al. (Limnology and Oceanography, 2023)
The Ruki is a pristine blackwater tributary in the Congo Basin draining tropical lowland forest. Daily discharge and fortnightly concentrations, isotopic ratios, and molecular composition of carbon and organic matter were measured for 1 yr (2019–2020). Like the Congo River, discharge peaked from November–January, with a smaller secondary peak in June. Dissolved organic carbon (DOC), inorganic carbon (DIC), carbon dioxide ( p CO 2 ), and methane ( p CH 4 ) concentrations were high (21.3 ± 4.8 mg C L −1 , 5.8 ± 0.9 mg C L −1 , 6370 ± 1740 ppm, and 250 ± 100 ppm, respectively) and positively correlated with discharge, indicating transport limitation. Total suspended solids and particulate organic carbon (POC) concentrations were generally low (3.68 ± 1.61 mg L −1 , 0.88 ± 0.33 mg C L −1 , respectively) and varied inversely with discharge, indicating source limitation. The Ruki exported a total of 3.25 Tg C yr −1 , of which DOC, DIC, and POC comprised 76%, 20%, and 3%, respectively. This DOC flux represents ~ 20% of the annual Congo Basin flux from about 5% of its area, highlighting the high yield. Isotopic ratios of DOC and POC indicate modern C3 forest vegetation as a source, except for a few older samples potentially indicating peat inputs. The bulk molecular composition of dissolved organic matter was seasonally consistent; however, a more oxidized and aromatic assemblage occurred at high discharge, corresponding with forest vegetation, while a more aliphatic, nitrogen‐, and sulfur‐enriched assemblage was found during low discharge, corresponding with soil‐derived organic matter. Overall, these results underscore how hydrology controls C concentrations in the Ruki River and how this blackwater river contributes disproportionately to C export per unit area within the Congo Basin hydrosystem.

Alpha-ketoglutaric acid mitigates the detrimental effects of soy antigenic protein on the intestinal health and growth performance of Mirror carp Cyprinus carpio - Zuliang Zhou; Jianhua Zhao; Clement R. de Cruz; Hong Xu; Liansheng Wang; Qiyou Xu (Fish Physiology and Biochemistry, 2023)

Biological and physical selectors for mobile biofilms, aerobic granules, and densified-biological flocs in continuously flowing wastewater treatment processes: A state-of-the-art review - Glen T. Daigger; Jacqueline Kuo; Nicolas Derlon; Dwight Houweling; Jose A. Jimenez; Bruce R. Johnson; James P. McQuarrie; Sudhir Murthy; Pusker Regmi; Clement Roche; Belinda Sturm; Bernhard Wett; et al. (Water Research, 2023)

Features of turbulence during wildland fires in forested and grassland environments - Ajinkya Desai; Warren E. Heilman; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Craig B. Clements; Tirtha Banerjee (Agricultural and Forest Meteorology, 2023)

Sustained secretion of human growth hormone from TheraCyte devices encapsulated with PiggyBac-engineered retinal pigment epithelium cells - Claudia R. Cecchi; Sidsel Alsing; Gustavo P.P. Jesus; Enio A. Zacarias; Lisbeth Kjaer; Michelle S. Clement; Makiko Kumagai-Braesch; Thomas J. Corydon; Paolo Bartolini; Cibele N. Peroni; Lars Aagaard (Tissue and Cell, 2023)

Assimilation of Blended Satellite Soil Moisture Data Products to Further Improve Noah-MP Model Skills - Jifu Yin; Xiwu Zhan; Michael Barlage; Sujay Kumar; Andrew Fox; Clement Albergel; Christopher R. Hain; Ralph R. Ferraro; Jicheng Liu (Journal of Hydrology, 2023)

Towards the fully automated monitoring of ecological communities - Marc Besson; Jamie Alison; Kim Bjerge; Thomas E. Gorochowski; Toke T. Høye; Tommaso Jucker; Hjalte M. R. Mann; Christopher F. Clements (Ecology Letters, 2022)
High‐resolution monitoring is fundamental to understand ecosystems dynamics in an era of global change and biodiversity declines. While real‐time and automated monitoring of abiotic components has been possible for some time, monitoring biotic components—for example, individual behaviours and traits, and species abundance and distribution—is far more challenging. Recent technological advancements offer potential solutions to achieve this through: (i) increasingly affordable high‐throughput recording hardware, which can collect rich multidimensional data, and (ii) increasingly accessible artificial intelligence approaches, which can extract ecological knowledge from large datasets. However, automating the monitoring of facets of ecological communities via such technologies has primarily been achieved at low spatiotemporal resolutions within limited steps of the monitoring workflow. Here, we review existing technologies for data recording and processing that enable automated monitoring of ecological communities. We then present novel frameworks that combine such technologies, forming fully automated pipelines to detect, track, classify and count multiple species, and record behavioural and morphological traits, at resolutions which have previously been impossible to achieve. Based on these rapidly developing technologies, we illustrate a solution to one of the greatest challenges in ecology: the ability to rapidly generate high‐resolution, multidimensional and standardised data across complex ecologies.

Sources of variation in community composition of the hindgut microbiota in two tropical Kyphosus species - Alessandro Pisaniello; Lilly D. Bojarski; Kim M. Handley; W. Lindsey White; Esther R. Angert; Kendall D. Clements (Coral Reefs, 2022)
Gut microbiota play a fundamental role in the nutrition of many vertebrate herbivores through foregut and hindgut fermentation of plant carbohydrates. Some species of marine herbivorous fishes contain moderate to high levels of short-chain fatty acids in the hindgut, indicating the importance of hindgut fermentation. Herbivorous fish hindgut microbiota are diverse and can vary with geographic location, but data on the scale of geographic variation involving a few km of separation are limited. Here, we used the 16S rRNA gene to describe community composition of the gut microbiota of the herbivorous species Kyphosus vaigiensis and K. cinerascens collected in the vicinity of Lizard Island, northern Great Barrier Reef, Australia, in 2011 and 2017. Microbiota community structure differed between posterior hindgut sections, host species, sampling years and two mid-shelf and outer reef locations approximately 20 km apart. Hindgut bacterial community composition varied remarkably between mid-shelf and outer reef locations, and among individual fish on the mid-shelf reef. In both fish species, the most abundant phyla were Pseudomonadota, Bacillota and Bacteroidota, followed by Spirochaetota, Thermodesulfobacteriota and Verrucomicrobiota. There were no clear differences between the host species in terms of the relative abundance and composition of bacterial genera in outer reef samples. In contrast, the dominant genera differed between mid-shelf samples of K. cinerascens and K. vaigiensis , being Endozoicomonas- like (Pseudomonadota) and Brevinema (Spirochaetota), respectively. Endozoicomonas are emerging as important symbionts in many marine hosts worldwide and are thought to be important in the coral sulphur cycle. Differences in microbiota composition were not associated with variation in fish condition, suggesting that the different microbial taxa perform equivalent functional roles.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

Distinct microbiota composition and fermentation products indicate functional compartmentalization in the hindgut of a marine herbivorous fish - Bikiran Pardesi; Anthony M. Roberton; Kevin C. Lee; Esther R. Angert; Douglas I. Rosendale; Svetlana Boycheva; William L. White; Kendall D. Clements (Molecular Ecology, 2022)
Many marine herbivorous fishes harbour diverse microbial communities in the hindgut that can play important roles in host health and nutrition. Kyphosus sydneyanus is a temperate marine herbivorous fish that feeds predominantly on brown seaweeds. We employed 16S rRNA gene amplicon sequencing and gas chromatography to characterize microbial communities and their metabolites in different hindgut regions of six K . sydneyanus . Measurements were confined to three distal sections of the intestine, labelled III, IV and V from anterior to posterior. A total of 625 operational taxonomic units from 20 phyla and 123 genera were obtained. Bacteroidota, Firmicutes and Proteobacteria were the major phyla in mean relative abundance, which varied along the gut. Firmicutes (76%) was the most dominant group in section III, whereas Bacteroidota (69.3%) dominated section V. Total short‐chain fatty acid (SCFA) concentration was highest in sections IV and V, confirming active fermentation in these two most distal sections. The abundance of Bacteroidota correlated with propionate concentration in section V, while Firmicutes positively correlated with formate in sections III and IV. Acetate levels were highest in sections IV and V, which correlated with abundance of Bacteroidota. Despite differences in gut microbial community composition, SCFA profiles were consistent between individual fish in the different hindgut regions of K . sydneyanus , although proportions of SCFAs differed among gut sections. These findings demonstrate functional compartmentalization of the hindgut microbial community, highlighting the need for regional sampling when interpreting overall microbiome function. These results support previous work suggesting that hindgut microbiota in marine herbivorous fish are important to nutrition in some host species by converting dietary carbohydrates into metabolically useful SCFAs.

Anti-drug Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Kelli Phillips; Charles Scott Hottenstein; Paul Chamberlain; Viswanath Devanaryan; Carol Gleason; Joanne Goodman; Marta Starcevic Manning; Shobha Purushothama; Susan Richards; Honglue Shen; et al. (The AAPS Journal, 2022)
Evolving immunogenicity assay performance expectations and a lack of harmonized anti-drug antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. Following debate at the American Association of Pharmaceutical Sciences National Biotechnology Conference, a group was formed to address these gaps. Over the last 3 years, 44 members from 29 organizations (including 5 members from Europe and 10 members from FDA) discussed gaps in understanding immunogenicity assay requirements and have developed harmonization tools for use by industry scientists to facilitate filings to health authorities. Herein, this team provides testing and reporting strategies and tools for the following assessments: (1) pre-study validation cut point; (2) in-study cut points, including procedures for applying cut points to mixed populations; (3) system suitability control criteria for in-study plate acceptance; (4) assay sensitivity, including the selection of an appropriate low positive control; (5) specificity, including drug and target tolerance; (6) sample stability that reflects sample storage and handling conditions; (7) assay selectivity to matrix components, including hemolytic, lipemic, and disease state matrices; (8) domain specificity for multi-domain therapeutics; (9) and minimum required dilution and extraction-based sample processing for titer reporting. Graphical Abstract

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

The killer within: Endogenous bacteria accelerate oyster mortality during sustained anoxia - Michael R. S. Coffin; Jeff C. Clements; Luc A. Comeau; Thomas Guyondet; Michelle Maillet; Laura Steeves; Keryn Winterburn; José M. F. Babarro; Martin A. Mallet; Rémy Haché; Luke A. Poirier; Saswati Deb; et al. (Limnology and Oceanography, 2021)
Sustained periods of anoxia, driven by eutrophication, threaten coastal marine systems and can lead to mass mortalities of even resilient animals such as bivalves. While mortality rates under anoxia are well‐studied, the specific mechanism(s) of mortality are less clear. We used a suite of complementary techniques (LT50, histology, 16S rRNA amplicon sequencing, and valvometry) to show that the proliferation of anaerobic bacteria within eastern oysters ( Crassostrea virginica ) accelerates mortality rate under anoxic conditions. Manipulative laboratory experiments revealed that oyster survival under anoxic conditions was halved when bacteria were present compared to when they were excluded by the broad‐spectrum antibiotic chloramphenicol. Histological assessments supported this mechanism and showed infiltration of bacteria in oysters that were not treated with antibiotics compared to a general lack of bacteria when oysters were treated with antibiotics. 16S rRNA amplicon sequencing failed to identify any particular genera of bacteria responsible for mortality, rather a diversity of endogenous anaerobic and/or sulfate‐reducing bacteria were common among oysters. In addition, monitoring of oyster valve gaping behavior in the field revealed that oysters showed remarkable valve closure synchrony when first exposed to anoxia. However, oysters periodically opened throughout anoxia/hypoxia in both the lab and field, suggesting that the infiltration of exogenous bacteria from the environment may also influence mortality rates under natural settings. Coupled with previous studies, we posit that mass mortality events in a wide range of coastal bivalves are likely the result of co‐morbidity from asphyxiation and bacterial processes.

Modeling Seasonal Distribution of Irrawaddy Dolphins (Orcaella brevirostris) in a Transnational Important Marine Mammal Area - Gregory M. Verutes; Sarah E. Tubbs; Nick Selmes; Darren R. Clark; Peter Walker; Oliver Clements (Frontiers in Marine Science, 2021)
Fishing activities continue to decimate populations of marine mammals, fish, and their habitats in the coastal waters of the Kep Archipelago, a cluster of tropical islands on the Cambodia-Vietnam border. In 2019, the area was recognized as an Important Marine Mammal Area, largely owing to the significant presence of Irrawaddy dolphins ( Orcaella brevirostris ). Understanding habitat preferences and distribution aids in the identification of areas to target for monitoring and conservation, which is particularly challenging in data-limited nations of Southeast Asia. Here, we test the hypothesis that accurate seasonal habitat models, relying on environmental data and species occurrences alone, can be used to describe the ecological processes governing abundance for the resident dolphin population of the Kep Archipelago, Cambodia. Leveraging two years of species and oceanographic data—depth, slope, distance to shore and rivers, sea surface temperature, and chlorophyll-a concentration—we built temporally stratified models to estimate distribution and infer seasonal habitat importance. Overall, Irrawaddy dolphins of Kep displayed habitat preferences similar to other populations, and were predominately encountered in three situations: (1) water depths ranging from 3.0 to 5.3 m, (2) surface water temperatures of 27–32°C, and (3) in close proximity to offshore islands (< 7.5 km). With respect to seasonality, statistical tests detected significant differences for all environment variables considered except seafloor slope. Four predictor sets, each with a unique combination of variables, were used to map seasonal variation in dolphin habitat suitability. Models with highest variable importance scores were water depth, pre- and during monsoon season (61–62%), and sea surface temperature, post-monsoon (71%), which suggests that greater freshwater flow during the wet season may alter primary productivity and dolphin prey abundance. Importantly, findings show the majority of areas with highest habitat suitability are not currently surveyed for dolphins and located outside Kep’s Marine Fisheries Management Area. This research confirms the need to expand monitoring to new areas where high-impact fisheries and other human activities operate. Baseline knowledge on dolphin distribution can guide regional conservation efforts by taking into account the seasonality of the species and support the design of tailored management strategies that address transboundary threats to an Important Marine Mammal Area.

Climate change in the context of whole-farming systems: opportunities for improved outreach - R. S. Clements; S. K. Birthisel; A. Daigneault; E. Gallandt; D. Johnson; T. Wentworth; M. T. Niles (Climatic Change, 2021)
Climate change poses a challenge to farming systems worldwide. However, existing research suggests that farmers and those providing outreach may have different climate change perspectives, and there is little understanding of how farmers prioritize climate change compared with other aspects of their farming system. To compare how farmers and outreach professionals in northern New England consider climate change within the context of whole-farming systems, we conducted mental modeling interviews with 33 farmers and 16 outreach professionals. Despite being primed to consider climate during the interviews, only 24% of farmers and 25% of outreach professionals included climate in their mental models. Key differences arose in both group’s perceptions of weather: outreach professionals focused on connections between good weather and biophysical factors, while farmers drew additional connections to factors like quality of life and overall farm success . Social factors including community well-being , public education , and farm success were significantly more likely to be included ( P < 0.05), and in some cases were more influential, in farmer models compared to outreach professional models. We conclude that farmer participants did not perceive climate to be a central factor of their farming systems, and valued human and social dimensions more highly than outreach professionals perceived. These factors may warrant special consideration in efforts to make outreach meaningful to local contexts, along with framing climate change within its broader relationship to other farming system aspects. Interdisciplinary teams may be helpful in developing outreach approaches that fully contextualize climate change within farmers’ complex whole-farm management perspectives.

Genetic structure and diversity identify incipient domestication of Piquiá [Caryocar villosum (Aubl.) pers.] along the lower Tapajós River, Brazilian Amazonia - Ana Flávia Francisconi; Rubana Palhares Alves; Charles R. Clement; Gabriel Dequigiovanni; Igor A. S. de Carvalho; Elizabeth A. Veasey (Genetic Resources and Crop Evolution, 2021)

Finding incident cancer cases through outpatient oncology clinic claims data and integration into a state cancer registry - Christopher R. Cogle; Gary Levin; David J. Lee; Steven Peace; Megsys C. Herna; Jill MacKinnon; Clement K. Gwede; Celeste Philip; Tara Hylton (Cancer Causes & Control, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Convergence, continuity, and community: a framework for enabling emerging leaders to build climate solutions in agriculture, forestry, and aquaculture - S. K. Birthisel; B. A. Eastman; A. R. Soucy; M. Paul; R. S. Clements; A. White; M. P. Acquafredda; W. Errickson; L-H. Zhu; M. C. Allen; S. A. Mills; G. Dimmig; et al. (Climatic Change, 2020)

Pre-Columbian soil fertilization and current management maintain food resource availability in old-growth Amazonian forests - Carolina Levis; Marielos Peña-Claros; Charles R. Clement; Flavia R. C. Costa; Rubana Palhares Alves; Maria Julia Ferreira; Camila Guarim Figueiredo; Frans Bongers (Plant and Soil, 2020)
Aims The extent and persistence of pre-Columbian human legacies in old-growth Amazonian forests are still controversial, partly because modern societies re-occupied old settlements, challenging the distinction between pre- and post-Columbian legacies. Here, we compared the effects of pre-Columbian vs. recent landscape domestication processes on soils and vegetation in two Amazonian regions. Methods We studied forest landscapes at varying distances from pre-Columbian and current settlements inside protected areas occupied by traditional and indigenous peoples in the lower Tapajós and the upper-middle Madeira river basins. By conducting 69 free-listing interviews, participatory mappings, guided-tours, 27 forest inventories, and soil analysis, we assessed the influences of pre-Columbian and current activities in soils and plant resources surrounding the settlements. Results In both regions, we found that pre-Columbian villages were more densely distributed across the landscape than current villages. Soil nutrients (mainly Ca and P) were higher closer to pre-Columbian villages but were generally not related to current villages, suggesting past soil fertilization. Soil charcoal was frequent in all forests, suggesting frequent fire events. The density of domesticated plants used for food increased in phosphorus enriched soils. In contrast, the density of plants used for construction decreased near current villages. Conclusions We detected a significant effect of past soil fertilization on food resources over extensive areas, supporting the hypothesis that pre-Columbian landscape domestication left persistent marks on Amazonian landscapes. Our results suggest that a combination of pre-Columbian phosphorus fertilization with past and current management drives plant resource availability in old-growth forests.

Genomic Diversity of Three Brazilian Native Food Crops Based on Double-Digest Restriction Site-Associated DNA Sequencing - Alessandro Alves-Pereira; Mariana Novello; Gabriel Dequigiovanni; José Baldin Pinheiro; Pedro H. S. Brancalion; Elizabeth Ann Veasey; Charles R. Clement; Anete Pereira de Souza; Maria Imaculada Zucchi (Tropical Plant Biology, 2019)

Genetic diversity and population structure show different patterns of diffusion for bitter and sweet manioc in Brazil - Gilda Santos Mühlen; Alessandro Alves-Pereira; Cássia Regina Limonta Carvalho; André Braga Junqueira; Charles R. Clement; Teresa Losada Valle (Genetic Resources and Crop Evolution, 2019)

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Report on the AAPS Immunogenicity Guidance Forum - Heather Myler; Boris Gorovits; Kelli Phillips; Viswanath Devanarayan; Adrienne Clements-Egan; George R. Gunn; Susan Kirshner; Binodh DeSilva; Vinod P. Shah (The AAPS Journal, 2019)

Presence and distribution of progerin in HGPS cells is ameliorated by drugs that impact on the mevalonate and mTOR pathways - Craig S. Clements; Mehmet U. Bikkul; Wendy Ofosu; Christopher Eskiw; David Tree; Evgeny Makarov; Ian R. Kill; Joanna M. Bridger (Biogerontology, 2019)

The role of fertile anthropogenic soils in the conservation of native and exotic agrobiodiversity in Amazonian homegardens - Nathalia B. de Souza; André Braga Junqueira; Paul C. Struik; Tjeerdjan Stomph; Charles R. Clement (Agroforestry Systems, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Bone marrow-derived stem/stromal cells (BMSC) 3D microtissues cultured in BMP-2 supplemented osteogenic induction medium are prone to adipogenesis - K. Futrega; E. Mosaad; K. Chambers; W. B. Lott; J. Clements; M. R. Doran (Cell and Tissue Research, 2018)

Farnesyltransferase inhibitor and rapamycin correct aberrant genome organisation and decrease DNA damage respectively, in Hutchinson–Gilford progeria syndrome fibroblasts - Mehmet U. Bikkul; Craig S. Clements; Lauren S. Godwin; Martin W. Goldberg; Ian R. Kill; Joanna M. Bridger (Biogerontology, 2018)

Erythropoietin Upregulates Brain Hemoglobin Expression and Supports Neuronal Mitochondrial Activity - N. K. Singhal; K. Alkhayer; J. Shelestak; R. Clements; E. Freeman; J. McDonough (Molecular Neurobiology, 2018)

Carbon emissions from South‐East Asian peatlands will increase despite emission‐reduction schemes - Lahiru S. Wijedasa; Sean Sloan; Susan E. Page; Gopalasamy R. Clements; Massimo Lupascu; Theodore A. Evans (Global Change Biology, 2018)
Carbon emissions from drained peatlands converted to agriculture in South‐East Asia (i.e., Peninsular Malaysia, Sumatra and Borneo) are globally significant and increasing. Here, we map the growth of South‐East Asian peatland agriculture and estimate CO 2 emissions due to peat drainage in relation to official land‐use plans with a focus on the reducing emissions from deforestation and degradation ( REDD +)‐related Indonesian moratorium on granting new concession licences for industrial agriculture and logging. We find that, prior to 2010, 35% of South‐East Asian peatlands had been converted to agriculture, principally by smallholder farmers (15% of original peat extent) and industrial oil palm plantations (14%). These conversions resulted in 1.46–6.43 Gt CO 2 of emissions between 1990 and 2010. This legacy of historical clearances on deep‐peat areas will contribute 51% (4.43–11.45 Gt CO 2 ) of projected future peatland CO 2 emissions over the period 2010–2130. In Indonesia, which hosts most of the region's peatland and where concession maps are publicly available, 70% of peatland conversion to agriculture occurred outside of known concessions for industrial plantation development, with smallholders accounting for 60% and industrial oil palm accounting for 34%. Of the remaining Indonesian peat swamp forest ( PSF ), 45% is not protected, and its conversion would amount to CO 2 emissions equivalent to 0.7%–2.3% (5.14–14.93 Gt) of global fossil fuel and cement emissions released between 1990 and 2010. Of the peatland extent included in the moratorium, 48% was no longer forested, and of the PSF included, 40%–48% is likely to be affected by drainage impacts from agricultural areas and will emit CO 2 over time. We suggest that recent legislation and policy in Indonesia could provide a means of meaningful emission reductions if focused on revised land‐use planning, PSF conservation both inside and outside agricultural concessions, and the development of agricultural practices based on rehabilitating peatland hydrological function.

Diet, the intestinal microbiota, and immune health in aging - Sarah J. Clements; Simon R. Carding (Critical Reviews in Food Science and Nutrition, 2018)

Acute and repetitive fronto-cerebellar tDCS stimulation improves mood in non-depressed participants - Simon Newstead; Hayley Young; David Benton; Gabriela Jiga-Boy; Maria L. Andrade Sienz; R. M. Clement; Frédéric Boy (Experimental Brain Research, 2018)

Host taxonomy constrains the properties of trophic transmission routes for parasites in lake food webs - Alyssa R. Cirtwill; Clement Lagrue; Robert Poulin; Daniel B. Stouffer (Ecology, 2017)
Some parasites move from one host to another via trophic transmission, the consumption of the parasite (inside its current host) by its future host. Feeding links among free‐living species can thus be understood as potential transmission routes for parasites. As these links have different dynamic and structural properties, they may also vary in their effectiveness as trophic transmission routes. That is, some links may be better than others in allowing parasites to complete their complex life cycles. However, not all links are accessible to parasites as most are restricted to a small number of host taxa. This restriction means that differences between links involving host and non‐host taxa must be considered when assessing whether transmission routes for parasites have different food web properties than other links. Here we use four New Zealand lake food webs to test whether link properties (contribution of a link to the predator's diet, prey abundance, prey biomass, amount of biomass transferred, centrality, and asymmetry) affect trophic transmission of parasites. Critically, we do this using both models that neglect the taxonomy of free‐living species and models that explicitly include information about which free‐living species are members of suitable host taxa. Although the best‐fit model excluding taxonomic information suggested that transmission routes have different properties than other feeding links, when including taxonomy, the best‐fit model included only an intercept. This means that the taxonomy of free‐living species is a key determinant of parasite transmission routes and that food‐web properties of transmission routes are constrained by the properties of host taxa. In particular, many intermediate hosts (prey) attain high biomasses and are involved in highly central links while links connecting intermediate to definitive (predator) hosts tend to be dynamically weak.

Responses of soil extracellular enzyme activities to experimental warming and CO2 enrichment at the alpine treeline - Rômulo C. Souza; Emily F. Solly; Melissa A. Dawes; Frank Graf; Frank Hagedorn; Simon Egli; Charles R. Clement; Laszlo Nagy; Christian Rixen; Martina Peter (Plant and Soil, 2017)

Opsins have evolved under the permanent heterozygote model: insights from phylotranscriptomics of Odonata - Anton Suvorov; Nicholas O. Jensen; Camilla R. Sharkey; M. Stanley Fujimoto; Paul Bodily; Haley M. Cahill Wightman; T. Heath Ogden; Mark J. Clement; Seth M. Bybee (Molecular Ecology, 2017)
Gene duplication plays a central role in adaptation to novel environments by providing new genetic material for functional divergence and evolution of biological complexity. Several evolutionary models have been proposed for gene duplication to explain how new gene copies are preserved by natural selection, but these models have rarely been tested using empirical data. Opsin proteins, when combined with a chromophore, form a photopigment that is responsible for the absorption of light, the first step in the phototransduction cascade. Adaptive gene duplications have occurred many times within the animal opsins’ gene family, leading to novel wavelength sensitivities. Consequently, opsins are an attractive choice for the study of gene duplication evolutionary models. Odonata (dragonflies and damselflies) have the largest opsin repertoire of any insect currently known. Additionally, there is tremendous variation in opsin copy number between species, particularly in the long‐wavelength‐sensitive ( LWS ) class. Using comprehensive phylotranscriptomic and statistical approaches, we tested various evolutionary models of gene duplication. Our results suggest that both the blue‐sensitive ( BS ) and LWS opsin classes were subjected to strong positive selection that greatly weakens after multiple duplication events, a pattern that is consistent with the permanent heterozygote model. Due to the immense interspecific variation and duplicability potential of opsin genes among odonates, they represent a unique model system to test hypotheses regarding opsin gene duplication and diversification at the molecular level.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

What a difference a bay makes: natural variation in dietary resources mediates growth in a recently settled herbivorous fish - Mark A. Priest; Andrew R. Halford; Kendall D. Clements; Emily Douglas; Sheena L. Abellana; Jennifer L. McIlwain (Coral Reefs, 2016)

Macroinvertebrate communities in spring-fed alpine source pools - A. R. Clements; P. J. Suter; M. Fussell; E. Silvester (Hydrobiologia, 2016)

Quantitative detection of viable helminth ova from raw wastewater, human feces, and environmental soil samples using novel PMA-qPCR methods - P. Gyawali; W. Ahmed; J. P. S. Sidhu; S. V. Nery; A. C. Clements; R. Traub; J. S. McCarthy; S. Llewellyn; P. Jagals; S. Toze (Environmental Science and Pollution Research, 2016)

Novel Conductive Carbon Black and Polydimethlysiloxane ECG Electrode: A Comparison with Commercial Electrodes in Fresh, Chlorinated, and Salt Water - Yeonsik Noh; Justin R. Bales; Bersain A. Reyes; Jennifer Molignano; Amanda L. Clement; George D. Pins; John P. Florian; Ki H. Chon (Annals of Biomedical Engineering, 2016)

Geographical distribution patterns of Carcharocles megalodon over time reveal clues about extinction mechanisms - Catalina Pimiento; Bruce J. MacFadden; Christopher F. Clements; Sara Varela; Carlos Jaramillo; Jorge Velez‐Juarbe; Brian R. Silliman (Journal of Biogeography, 2016)
Aim Given its catastrophic consequences, the extinction of apex predators has long been of interest to modern ecology. Despite major declines, no present‐day species of marine apex predator has yet become extinct. Because of their vulnerability, understanding the mechanisms leading to their extinction in the past could provide insight into the natural factors that interact with human threats to drive their loss. We studied the geographical distribution patterns of the extinct macro‐predatory shark Carcharocles megalodon in order to elucidate its pathway to extinction. Location World‐wide from the Miocene to the Pliocene ( c. 23–2.6 Ma). Methods A meta‐analysis of C. megalodon occurrence records was performed using the Paleobiology Database as a platform. The data were binned into geological time slices, and the circular home range around each data point was mapped in reconstructions made in GP lates. We then quantitatively assessed the species' geographical range and global abundance over time, and the relationship between distribution and climate. Results The pathway to extinction of C. megalodon probably started in the late Miocene with a decrease in its global abundance. This decrease was then followed by a decline in its geographical range during the Pliocene. Although the extinction of C. megalodon has been attributed to climate change, we found no evidence of direct effects of global temperature. Instead, we found that the collapse in geographical distribution coincided mainly with a drop in the diversity of filter‐feeding whales and the appearance of new competitors (large predatory whales and the great white shark). Main conclusions This research represents the first study of the distributional trends of an extinct, cosmopolitan apex predator in deep‐time. Our results suggest that biotic factors, and not direct temperature limitations, were probably the primary drivers of the extinction of the largest marine apex predators that ever lived.

Paradigms for parasite conservation - Eric R. Dougherty; Colin J. Carlson; Veronica M. Bueno; Kevin R. Burgio; Carrie A. Cizauskas; Christopher F. Clements; Dana P. Seidel; Nyeema C. Harris (Conservation Biology, 2016)
Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain understudied, underfunded, and underappreciated. We argue the protection of parasitic biodiversity requires a paradigm shift in the perception and valuation of their role as consumer species, similar to that of apex predators in the mid‐20th century. Beyond recognizing parasites as vital trophic regulators, existing tools available to conservation practitioners should explicitly account for the unique threats facing dependent species. We built upon concepts from epidemiology and economics (e.g., host‐density threshold and cost‐benefit analysis) to devise novel metrics of margin of error and minimum investment for parasite conservation. We define margin of error as the risk of accidental host extinction from misestimating equilibrium population sizes and predicted oscillations, while minimum investment represents the cost associated with conserving the additional hosts required to maintain viable parasite populations. This framework will aid in the identification of readily conserved parasites that present minimal health risks. To establish parasite conservation, we propose an extension of population viability analysis for host–parasite assemblages to assess extinction risk. In the direst cases, ex situ breeding programs for parasites should be evaluated to maximize success without undermining host protection. Though parasitic species pose a considerable conservation challenge, adaptations to conservation tools will help protect parasite biodiversity in the face of an uncertain environmental future.

Phytotoxicities of the invasive species Plantago major and non-invasive species Plantago asiatica - Hisashi Kato-Noguchi; Naoko Hamada; David R. Clements (Acta Physiologiae Plantarum, 2015)

A White Paper—Consensus and Recommendations of a Global Harmonization Team on Assessing the Impact of Immunogenicity on Pharmacokinetic Measurements - J. M. Sailstad; L. Amaravadi; A. Clements-Egan; B. Gorovits; H. A. Myler; R. C. Pillutla; S. Pursuhothama; M. Putman; M. K. Rose; K. Sonehara; L. Tang; J. T. Wustner (The AAPS Journal, 2014)

Intestinal microbiota in fishes: what's known and what's not - Kendall D. Clements; Esther R. Angert; W. Linn Montgomery; J. Howard Choat (Molecular Ecology, 2014)
High‐throughput sequencing approaches have enabled characterizations of the community composition of numerous gut microbial communities, which in turn has enhanced interest in their diversity and functional relationships in different groups of vertebrates. Although fishes represent the greatest taxonomic and ecological diversity of vertebrates, our understanding of their gut microbiota and its functional significance has lagged well behind that of terrestrial vertebrates. In order to highlight emerging issues, we provide an overview of research on fish gut microbiotas and the biology of their hosts. We conclude that microbial community composition must be viewed within an informed context of host ecology and physiology, and that this is of particular importance with respect to research planning and sampling design.

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Elevated prefrontal myo-inositol and choline following breast cancer chemotherapy - Shelli R. Kesler; Christa Watson; Della Koovakkattu; Clement Lee; Ruth O’Hara; Misty L. Mahaffey; Jeffrey S. Wefel (Brain Imaging and Behavior, 2013)

Coconuts in the Americas - Charles R. Clement; Daniel Zizumbo-Villarreal; Cecil H. Brown; R. Gerard Ward; Alessandro Alves-Pereira; Hugh C. Harries (The Botanical Review, 2013)

Why conservationists should be concerned about natural resource legislation affecting indigenous peoples’ rights: lessons from Peninsular Malaysia - Sheema A. Aziz; Gopalasamy R. Clements; D. M. Rayan; Preetha Sankar (Biodiversity and Conservation, 2013)

Environmental changes impacting Echinococcus transmission: research to support predictive surveillance and control - Jo‐An M. Atkinson; Darren J. Gray; Archie C.A. Clements; Tamsin S. Barnes; Donald P. McManus; Yu R. Yang (Global Change Biology, 2013)
Echinococcosis, resulting from infection with tapeworms Echinococcus granulosus and E. multilocularis, has a global distribution with 2–3 million people affected and 200,000 new cases diagnosed annually. Costs of treatment for humans and economic losses to the livestock industry have been estimated to exceed $2 billion. These figures are likely to be an underestimation given the challenges with its early detection and the lack of mandatory official reporting policies in most countries. Despite this global burden, echinococcosis remains a neglected zoonosis. The importance of environmental factors in influencing the transmission intensity and distribution of Echinococcus spp. is increasingly being recognized. With the advent of climate change and the influence of global population expansion, food insecurity and land‐use changes, questions about the potential impact of changing temperature, rainfall patterns, increasing urbanization, deforestation, grassland degradation and overgrazing on zoonotic disease transmission are being raised. This study is the first to comprehensively review how climate change and anthropogenic environmental factors contribute to the transmission of echinococcosis mediated by changes in animal population dynamics, spatial overlap of competent hosts and the creation of improved conditions for egg survival. We advocate rigorous scientific research to establish the causal link between specific environmental variables and echinococcosis in humans and the incorporation of environmental, animal and human data collection within a sentinel site surveillance network that will complement satellite remote‐sensing information. Identifying the environmental determinants of transmission risk to humans will be vital for the design of more accurate predictive models to guide cost‐effective pre‐emptive public health action against echinococcosis.

Remediation of Uranium-contaminated Groundwater by Sorption onto Hydroxyapatite Derived from Catfish Bones - S. A. Chattanathan; T. P. Clement; S. R. Kanel; M. O. Barnett; N. Chatakondi (Water, Air, & Soil Pollution, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Early Postnatal Ethanol Exposure: Glutamatergic Excitotoxic Cell Death During Acute Withdrawal - K. M. Clements; L. M. Smith; J. N. J. Reynolds; P. G. Overton; J. D. Thomas; R. M. Napper (Neurophysiology, 2012)

Acute and Chronic Effects of Sodium Tungstate on an Aquatic Invertebrate (Daphnia magna), Green Alga (Pseudokirchneriella subcapitata), and Zebrafish (Danio rerio) - Leslie N. Clements; Ranulfo Lemus; Alicia D. Butler; Kate Heim; Matthew R. Rebstock; Carmen Venezia; Michael Pardus (Archives of Environmental Contamination and Toxicology, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Genetic structure of traditional varieties of bitter manioc in three soils in Central Amazonia - Alessandro Alves-Pereira; Nivaldo Peroni; Aluana Gonçalves Abreu; Rogério Gribel; Charles R. Clement (Genetica, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Initiation of HAART during acute simian immunodeficiency virus infection rapidly controls virus replication in the CNS by enhancing immune activity and preserving protective immune responses - David R. Graham; Lucio Gama; Suzanne E. Queen; Ming Li; Angela K. Brice; Kathleen M. Kelly; Joseph L. Mankowski; Janice E. Clements; M. Christine Zink (Journal of NeuroVirology, 2011)

Temperature sensitivity of cardiac mitochondria in intertidal and subtidal triplefin fishes - Zoë Hilton; Kendall D. Clements; Anthony J. R. Hickey (Journal of Comparative Physiology B, 2010)

Secondary forests on anthropogenic soils in Brazilian Amazonia conserve agrobiodiversity - André Braga Junqueira; Glenn Harvey Shepard; Charles R. Clement (Biodiversity and Conservation, 2010)

Characterization of the carbon fluxes of a vegetated drained lake basin chronosequence on the Alaskan Arctic Coastal Plain - D. ZONA; W. C. OECHEL; K. M. PETERSON; R. J. CLEMENTS; K. T. PAW U; S. L. USTIN (Global Change Biology, 2010)
Greenhouse gas fluxes from vegetated drained lake basins have been largely unstudied, although these land features constitute up to 47% of the land cover in the Arctic Coastal Plain in northern Alaska. To describe current and to better predict future sink/source activity of the Arctic tundra, it is important to assess these vegetated drained lake basins with respect to the patterns of and controls on gross primary production (GPP), net ecosystem exchange, and ecosystem respiration (ER). We measured CO 2 fluxes and key environmental variables during the 2007 growing season (June through August) in 12 vegetated drained lake basins representing three age classes (young, drained about 50 years ago; medium, drained between 50 and 300 years ago; and old, drained between 300 and 2000 years ago, as determined by Hinkel et al. , 2003) in the Arctic Coastal Plain. Young vegetated drained lake basins had both the highest average GPP over the summer (11.4 gCO 2 m −2 day −1 ) and the highest average summer ER (7.3 gCO 2 m −2 day −1 ), while medium and old vegetated drained lake basins showed lower and similar GPP (7.9 and 7.2 gCO 2 m −2 day −1 , respectively), and ER (5.2 and 4 gCO 2 m −2 day −1 , respectively). Productivity decreases with age as nutrients are locked up in living plant material and dead organic matter. However, we showed that old vegetated drained lakes basins maintained relatively high productivity because of the increased development of ice‐wedge polygons, the formation of ponds, and the re‐establishment of very productive species. Comparison of the seasonal CO 2 fluxes and concomitant environmental factors over this chronosequence provides the basis for better understanding the patterns and controls on CO 2 flux across the coastal plain of the North Slope of Alaska and for more accurately estimating current and future contribution of the Arctic to the global carbon budget.

Hantavirus nephropathy as a pseudo-import pathology from Ecuador - R. Demeester; E. Bottieau; M. Van Esbroeck; M. R. Pourkarim; P. Maes; J. Clement (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Analysis of information used in the management of plant genetic resources: a case study from northwestern Mato Grosso, Brazil - Jorge L. Vivan; Peter H. May; Luís H. H. da Cunha; Walter S. de Boef; Charles R. Clement (Agroforestry Systems, 2009)

New Zealand triplefin fishes (family Tripterygiidae): contrasting population structure and mtDNA diversity within a marine species flock - ANTHONY J. R. HICKEY; SHANE D. LAVERY; DANIELLE A. HANNAN; C. SCOTT BAKER; KENDALL D. CLEMENTS (Molecular Ecology, 2009)
Triplefin fishes (Family Tripterygiidae) dominate the New Zealand temperate coastal fish fauna in diversity (26 endemic species, 14 genera). Most species appear to have evolved as a local radiation and mostly occupy sympatric distributions throughout New Zealand. To investigate the forces driving current gene‐flow patterns and past evolutionary histories, we searched for common patterns of population genetic subdivision within eight species sampled throughout their distributions [mitchochondrial DNA (mtDNA) control region, n = 1086]. We hypothesised that common phylogeographical and population differentiation patterns would reveal past or ongoing physical processes, with differences reflecting stochastic or species‐specific processes. Striking differences between species were apparent, with strong phylogeographical structure detected in Grahamina capito and the estuarine species G. nigripenne . G. capito fell into three distinct geographically restricted lineages. G. nigripenne largely separated into northern and southern lineages (Φ ST 0.834). Strong population structuring and isolation by distance was evident in Bellapiscis medius , B. lesleyae and Forsterygion lapillum (Φ ST 0.686, 0.436 and 0.115, respectively). High gene flow was apparent in G. gymnota and Ruanoho whero , and F. varium . However, for the latter species, isolation was apparent with samples collected from the offshore Three Kings Islands. Overall, a strong relationship was found between habitat depth and population structure among species, and species inhabiting shallower water habitats showed lower genetic diversity with higher levels of population subdivision. High‐latitude populations generally showed low haplotype and nucleotide diversity. These data suggest that processes resulting from intraspecific differences in habitat preference, climatic histories and/or larval ecologies have subdivided populations of shallow water triplefin species.

Changes in dissolved organic material determine exposure of stream benthic communities to UV‐B radiation and heavy metals: implications for climate change - WILLIAM H. CLEMENTS; MARJORIE L. BROOKS; DONNA R. KASHIAN; ROBERT E. ZUELLIG (Global Change Biology, 2008)
Changes in regional climate in the Rocky Mountains over the next 100 years are expected to have significant effects on biogeochemical cycles and hydrological processes. In particular, decreased discharge and lower stream depth during summer when ultraviolet radiation (UVR) is the highest combined with greater photo‐oxidation of dissolved organic materials (DOM) will significantly increase exposure of benthic communities to UVR. Communities in many Rocky Mountain streams are simultaneously exposed to elevated metals from abandoned mines, the toxicity and bioavailability of which are also determined by DOM. We integrated field surveys of 19 streams (21 sites) along a gradient of metal contamination with microcosm and field experiments conducted in Colorado, USA, and New Zealand to investigate the influence of DOM on bioavailability of heavy metals and exposure of benthic communities to UVR. Spatial and seasonal variation in DOM were closely related to stream discharge and significantly influenced heavy metal uptake in benthic organisms. Qualitative and quantitative changes in DOM resulting from exposure to sunlight increased UV‐B (290–320 nm) penetration and toxicity of heavy metals. Results of microcosm experiments showed that benthic communities from a metal‐polluted stream were tolerant of metals, but were more sensitive to UV‐B than communities from a reference stream. We speculate that the greater sensitivity of these communities to UV‐B resulted from costs associated with metal tolerance. Exclusion of UVR from 12 separate Colorado streams and from outdoor stream microcosms in New Zealand increased the abundance of benthic organisms (mayflies, stoneflies, and caddisflies) by 18% and 54%, respectively. Our findings demonstrate the importance of considering changes in regional climate and UV‐B exposure when assessing the effects of local anthropogenic stressors.

Development of SHRIMP - T. R. Ireland*; S. Clement; W. Compston; J. J. Foster; P. Holden; B. Jenkins; P. Lanc; N. Schram; I. S. Williams (Australian Journal of Earth Sciences, 2008)

Tannin impacts on microbial diversity and the functioning of alpine soils: a multidisciplinary approach - F. Baptist; L. Zinger; J. C. Clement; C. Gallet; R. Guillemin; J. M. F. Martins; L. Sage; B. Shahnavaz; Ph. Choler; R. Geremia (Environmental Microbiology, 2008)
Summary In alpine ecosystems, tannin‐rich‐litter decomposition occurs mainly under snow. With global change, variations in snowfall might affect soil temperature and microbial diversity with biogeochemical consequences on ecosystem processes. However, the relationships linking soil temperature and tannin degradation with soil microorganisms and nutrients fluxes remain poorly understood. Here, we combined biogeochemical and molecular profiling approaches to monitor tannin degradation, nutrient cycling and microbial communities (Bacteria, Crenarcheotes, Fungi) in undisturbed wintertime soil cores exposed to low temperature (0°C/−6°C), amended or not with tannins, extracted from Dryas octopetala . No toxic effect of tannins on microbial populations was found, indicating that they withstand phenolics from alpine vegetation litter. Additionally at −6°C, higher carbon mineralization, higher protocatechuic acid concentration (intermediary metabolite of tannin catabolism), and changes in fungal phylogenetic composition showed that freezing temperatures may select fungi able to degrade D. octopetala 's tannins. In contrast, negative net nitrogen mineralization rates were observed at −6°C possibly due to a more efficient N immobilization by tannins than N production by microbial activities, and suggesting a decoupling between C and N mineralization. Our results confirmed tannins and soil temperatures as relevant controls of microbial catabolism which are crucial for alpine ecosystems functioning and carbon storage.

Biology and molecular phylogenetics of Nematoceras sulcatum, a second endemic orchid species from subantarctic Macquarie Island - Mark A. Clements; Anne M. Mackenzie; Geof R. Copson; Brian P. J. Molloy; Noel Carmichael; Mary L. Skotnicki; Patricia M. Selkirk (Polar Biology, 2007)

Somatic embryogenesis from peach palm zygotic embryos - D. A. Steinmacher; G. C. Cangahuala-Inocente; C. R. Clement; M. P. Guerra (In Vitro Cellular & Developmental Biology - Plant, 2007)

Somatic embryogenesis from immature peach palm inflorescence explants: towards development of an efficient protocol - Douglas A. Steinmacher; Charles R. Clement; Miguel P. Guerra (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Nonlinear time series analysis of jerk congenital nystagmus - O. E. Akman; D. S. Broomhead; R. A. Clement; R. V. Abadi (Journal of Computational Neuroscience, 2006)

Facilitation of brain stimulation reward by MK-801 (dizocilpine) may be independent of D2-like dopamine receptor stimulation in rats - R. L. H. Clements; A. J. Greenshaw (Psychopharmacology, 2005)

Nitrosylhemoglobin as a Potential Bioactive Storage form of Nitric Oxide (NO) - F. Pirrone; M. Albertini; S. Mazzola; G. Aldini; M. Orioli; M. Carini; R. Maffei Facino; M. G. Clement (Veterinary Research Communications, 2005)

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

Differential effects of intra-midbrain raph and systemic 8-OH-DPAT on VTA self-stimulation thresholds in rats - K.-C. Ahn; H. Pazderka-Robinson; R. Clements; R. Ashcroft; T. Ali; C. Morse; A. J. Greenshaw (Psychopharmacology, 2005)

Molecular marker-mediated validation of morphologically defined landraces of Pejibaye (Bactris gasipaes) and their phylogenetic relationships - Doriane P. Rodrigues; Spartaco Astolfi Filho; Charles R. Clement (Genetic Resources and Crop Evolution, 2005)

Verifying invasive marine fish species using molecular techniques: A model example using triplefin fishes (Family Tripterygiidae) - Anthony J. R. Hickey; Shane D. Lavery; Sarah R. Eyton; Kendall D. Clements (New Zealand Journal of Marine and Freshwater Research, 2004)
Molecular techniques can resolve many questions concerning the identification and origins of invasive marine species. We used a molecular taxonomy based on the mitochondrial control region (mtCR) to identify the origin of three cryptogenic triplefin species (Family: Tripterygiidae) found in two Australian ports—Port Phillip Bay, Melbourne and the Derwent Estuary, Hobart. DNA was extracted from Australian specimens of Forsterygion varium, F. lapillum , and Grahamina gymnota , and PCR (polymerase chain reaction) fragments of the mitochondrial control region (mtCR, c. 400 bp) were amplified, sequenced, and aligned to a reference alignment containing 23 endemic New Zealand triplefin species. Multiple specimens were sequenced for Australian F. varium , and G. gymnota , and the sequences were aligned to data sets from conspecific specimens collected around New Zealand. The sequences from Australian specimens of F. varium and G. gymnota consisted of only one and two haplotypes, respectively. Haplotypes of all three Australian species nested among New Zealand conspecific haplotypes, and the single Australian F. varium haplotype was shared with two southern New Zealand individuals. The low genetic diversity in two of the Australian triplefin populations of F . varium and G. gymnota and their close genetic relationship to New Zealand populations strongly suggests recent introductions from New Zealand to Australia.

Operant responding for a visual reinforcer in rats is enhanced by noncontingent nicotine: implications for nicotine self-administration and reinforcement - Eric C. Donny; Nadia Chaudhri; Anthony R. Caggiula; F. Fay Evans-Martin; Sheri Booth; Maysa A. Gharib; Laure A. Clements; Alan F. Sved (Psychopharmacology, 2003)

High-mountain landslides in the Atlantic Pyrenees: their relationship with the geology and geomorphology - T. Lebourg; R. Fabre; B. Clement; M. Frappa (Bulletin of Engineering Geology and the Environment, 2003)

A Re-Evaluation of Long-Term Flux Measurement Techniques Part I: Averaging and Coordinate Rotation - J. J. Finnigan; R. Clement; Y. Malhi; R. Leuning; H.A. Cleugh (Boundary-Layer Meteorology, 2003)

Key metabolic enzymes and muscle structure in triplefin fishes (Tripterygiidae): a phylogenetic comparison - A. J. R. Hickey; K. D. Clements (Journal of Comparative Physiology B, 2003)

Central Nervous System Correlates of Behavioral Deficits Following Simian Immunodeficiency Virus Infection - Michael R Weed; Robert D Hienz; Joseph V Brady; Robert J Adams; Joseph L Mankowski; Janice E Clements; M Christine Zink (Journal of NeuroVirology, 2003)

Relation Between Near-Wall Residence Times of Monocytes and Early Lesion Growth in the Rabbit Aorto–Celiac Junction - P. Worth Longest; Clement Kleinstreuer; George A. Truskey; John R. Buchanan (Annals of Biomedical Engineering, 2003)

Measuring the Electrical Stapedius Reflex with Stapedius Muscle Electromyogram Recordings - Ryan S. Clement; Paul M. Carter; Daryl R. Kipke (Annals of Biomedical Engineering, 2002)

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

Modelling of congenital nystagmus waveforms produced by saccadic system abnormalities - David S. Broomhead; Richard A. Clement; Mark R. Muldoon; Jonathan P. Whittle; Columba Scallan; Richard V. Abadi (Biological Cybernetics, 2000)

Haemoglobin components and oxygen transport in relation to habitat distribution in triplefin fishes (Tripterygiidae) - O. Brix; K. D. Clements; R. M. G. Wells (Journal of Comparative Physiology B, 1999)

Dynamical systems analysis: a new method of analysing congenital nystagmus waveforms - R. V. Abadi; D. S. Broomhead; R. A. Clement; J. P. Whittle; R. Worfolk (Experimental Brain Research, 1997)

Methanol metabolism in thermotolerant methylotrophic Bacillus strains involving a novel catabolic NAD-dependent methanol dehydrogenase as a key enzyme - N. Arfman; E. M. Watling; W. Clement; R. J. van Oosterwijk; G. E. de Vries; W. Harder; M. M. Attwood; L. Dijkhuizen (Archives of Microbiology, 1989)

The potential use of the pejibaye palm in agroforestry systems - Charles R. Clement (Agroforestry Systems, 1988)

The pejibaye palm (Bactris gasipaes H.B.K.) as an agroforestry component - Charles R. Clement (Agroforestry Systems, 1986)